The Yugapad-Way Of Using Words: How a Linguistic Taboo Became a Crucial Literary Strategy - Pontillo, Tiziana (Lingua Posnaniensis, 2013)
As K ātyāyana emphasizes while commenting on the ekaśeṣa-rules, words apply per object. Consequently, no word should be capable of conveying more than one object. By contrast not only does paronomasia, the so-called śleṣa, break the one-to-one relation between the śabda- and artha-levels of language; there are also grammatical rules which look like deviations from the naturally expected cause-effect relation between word forms and their meanings. T he ekaśeṣa-rule represents one of these exceptions, since some parts of the artha are comprehensible, even without employing the word-form denoting them, such as mātṛ in the dual noun pitarau, meaning ‘mother and father’ rather than ‘the two fathers’. P atañjali already mentions an intriguing option in the use of śabdas, when he notes that a word form can merely convey its primary denotation, such as candra denoting the ‘moon’, or can express something that is ‘like something else’, such as candra conveying the sense of a ‘face like a moon’. These exceptions are reconsidered here within the framework of the “yugapad-expression”, which is how Bhartṛhari defines one of the two language options (the other one being kramaḥ ‘sequence’), an option realised when a single word simultaneously conveys more than one meaning, but an option whose use is discouraged. Technical (ritual and grammatical) speculations on simultaneity as an exception to the bi-unique relationship between a cause and its effect date back to the 2nd to 3rd centuries BC. N onetheless, grammarians insist on excluding these extreme applications of meaning extension; only the late kāvyālaṃkāraśāstra- authors extol the virtues of the phenomenon. T he paper focuses on the trajectory that might have been followed in the intervening changes.